Adjustment of the WACC with Subsidized Debt in the Presence of Corporate Taxes: The Finite-Horizon Case - Vélez-Pareja, Ignacio; Tham, Joseph; Fernández, Viviana (Estudios de Administración, 2005)
When discounting free-cash flows (FCF) at the Weighted Average Cost of Capital (WACC), we assume that the cost of debt is the market, unsubsidized rate. With debt at the market rate and perfect capital markets, debt only creates value in the presence of taxes through the tax shield. In some cases, the firm may be able to obtain a loan at a rate that is below the market rate. With subsidized debt and taxes, there would be a benefit to debt financing, and the unleveraged and leveraged values of the cash flows would differ. The benefit of lower tax savings are offset by the benefit of the subsidy. These two benefits have to be introduced explicitly. In this article, we present the necessary adjustments to the WACC and the cost of leveraged equity under the existence of subsidized debt and taxes in a multiple-period setting. We analyze the cases of the WACC applied to the FCF and the WACC applied to the capital-cash flows (CCF). We also utilize the Adjusted Present Value (APV) to consider both the tax savings and the subsidy. We show that all these different approaches give the same answer.